KEWENANGAN BADAN LAYANAN UMUM DALAM PENGELOLAAN KEUANGAN NEGARA: Febry Heriansyah - admin, admin (Reformasi Hukum, 2017)
The formation of BLU aims to improve services to the public in the form of the provision of goods and / or services in order to advance the general welfare and educate the life of the nation by providing flexibility in managing state finances based on economic principles and productivity. From some opinions the legal experts show that the authority of the BLU is a legal-rational authority obtained through the delegation of authority so that in carrying out its legal actions must pay attention to the rules and procedures of the law. And in terms of legal standing, BLU is not a legal entity but an extension agent of public (state) legal subjects, this is seen from BLU's wealth which is a state asset that is not separated